The Extent of Forest Fire, Grazing and Regeneration Status in Inventoried Forest Areas of India - Rai, S. N.; Saxena, Alok (Indian Forester, 1997)
Forest fires and indiscrimate grazing are among the most important factors that affect the natural regeneration in the forests and cause its degradation. Results of the inventories carried out by the Forest Survey of India show that on an average 54.7% of the forest is affected by fire, 77.6% area has grazing incidence and 72.1% forest area has no regeneration. These results further reveal that moist deciduous forests have more incidences offire while dry-deciduous and thorny forests are more subjected to grazing.